Advanced accounting - Fischer, Paul M.; Taylor, William J.; Cheng, Rita H. (Cincinnati : South-Western College, 1998)
This book is divided into six parts: Combined corporate entities and consolidations; Multinational accounting; Special reporting concerns; Partnerships; Governmental and Not-for-Profit accounting; and Fiduciary Accounting.
Keywords: Accounting; Accounting